ANALISIS MODEL PASIEN RAWAT JALAN RUMAH SAKIT KARIADI DENGAN PENDEKATAN POISSON-EKSPONENSIAL - Dwi Ispriyanti; Sugito Sugito; Agus Rusgiyono (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
In daily activities, we often face in a situation of queuing. Most people have experiences in a queuing situation or a waiting situation . The queuing can be found easily in a human life. For example is the queuing in the Kariadi Hospital. The Queuing occur from the registration to the service stage. Similarly, in ambulatory patients of Kariadi Hospital, so it is necessary to analyze the queuing effectivity, whether the queueing system is optimal or not. One of the statistical methods to analyze the things mentioned above are queuing theory. This research is used to analyze the queuing service system at the Kariadi hospital Keywords: Kariadi Hospital, The Queuing